WOMAN IMAGES IN INDONESIAN LITERATURE - Siti Aisah Ginting (BAHAS, 2019)
Abstrak This study was aimed to describe the woman images in Indonesian Literature. The data used the word and sentences choices that were taken from some poems and prose. The result of the study showed that the woman images still in less fortunate position Kata Kunci : image, literature